No difference on the level of PGC1A MRNA experssion after two radically different high intensity training sessions in highly trained cyclists - Westergren, J.; Psilander, N.; Wang, L.; Knutsson, M.; Sahlin, K.; Tonkonogi, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In recent years a number of studies on high intensity interval training have shown that a very limited number of wingate type intervals performed over only a few weeks can improve endurance performance dramatically. Since PGC1a is a major regulator of mitochondrial biogenesis, we hypothesized that there would be no difference in PGC1a mRNA expression between wingate type intervals and longer lower intensity intervals. The aim of this study was to compare the impact on the level of PGC1a mRNA expression of two radically different high intensity interval training sessions in highly trained cyclists. Ten male cyclists, (mean±SD) age 24.7± 4.4 years, height 179.1±4.8 cm, weight 70.1±6.2 kg, VO2peak 4753±470 ml min-1, Wmax 403±40 W volunteered for the study. After a standardized 15 min warm up, the subjects performed the following radically different high intensity interval training sessions, on a Cyclus 2 ergometer, 7-9 days apart in a counterbalanced fashion. The short interval high intensity training session consisted of 7 maximal 30 seconds isocadence sprints at 110 rpm separated by 4 minutes of active recovery at 50W. The long interval high intensity training session consisted of 3 time trials of 20 minute duration separated by 4 minutes of active recovery at 50W. Subjects were instructed to try and achieve to highest possible average power during all three intervals. The effective work duration for the short and long intervals was 3.5 minutes and 60 minutes respectively. Needle biopsies were obtained from M.Vastus Lateralis muscle at 15 minutes prior to the training session and 3 hours after completion of the training session. Average power output, capillary blood lactate levels and PGC1a mRNA expression of the short and long high intensity training session was 643±71 W, 14.9±2.4 mmol L-1, 6.03±1.8 fold change and 304±38W, 4.4±1.3 mmol L-1, 6.59±2.45 fold change respectively, with significant differences between the two sessions for power output and blood lactate levels but not for PGC1a mRNA expression. Despite the radical difference of the high intensity training sessions in terms of power output and blood lactate levels there is no difference in PGC1a mRNa expression. Meaning that both types of high intensity training sessions may provide similar stimuli for mitochondrial biogenesis.